Urban–rural disparity in prevalence of multimorbidity in China: a cross-sectional nationally representative study - Ma, Xiaochen (BMJ Open, 2020)
BACKGROUND: To address the neglect of depression in multimorbidity measurement and the lack of focus on rural population in previous literature about China, this paper aimed to estimate the prevalence of multimorbidity (including depressive disorders) among the country’s rural and urban population. METHODS: We used a cross-sectional design and data from a nationally representative survey conducted in 2015–2016 among Chinese people aged 45 years or older involving 19 656 participants. Multimorbidity was measured with a cut-off point of having two or more among 14 chronic illnesses. In that 13 of them were based on self-reported physician diagnosis. In addition, depressive disorders were assessed with the 10-item Centre for Epidemiologic Studies Depression Scale. The weighted prevalence of multimorbidity was calculated, with a non-response adjustment. Multivariate logistic regression was applied to analyse the relation between covariates and multimorbidity. FINDINGS: Multimorbidity was highly prevalent (54.3%) among the studied population. Contrary to previous studies, we found the prevalence of multimorbidity to be higher among the rural dwellers (58.3%) than among the urban population (50.4%). After adjustment for covariates, rural residents had 7.5% higher odds (95% CI of OR (1.003 to 1.151)) of having multimorbidity than their urban counterparts. Above 70% of patients with any of the 14 chronic illnesses above 45 years old had multimorbidity, while 80.6%–97.9% of chronic patients had multimorbidity. INTERPRETATION: Future health system development in China should transform from preventing and controlling non-communicable diseases as individual diseases to addressing people’s comprehensive health needs under multimorbidity. The rural population should be prioritised as they suffered more from multimorbidity than the urban population.